Therapeutic environments as a catalyst for health, well-being and social equity. (18th August 2021) - Marques, Bruno; McIntosh, Jacqueline; Kershaw, Chelsea
ABSTRACT: With the increasing prevalence of mental illness, there is an ever-growing need for supportive and rehabilitative social and health services and facilities. In many countries, the healthcare infrastructure, transitional services and communities are isolated from one another, creating physical and mental barriers to rehabilitation. Therapeutic landscape research suggests that outdoor spaces can facilitate rehabilitative healing, foster community support and self-empowerment. Design focused on facilitating preventative and rehabilitative health may bridge the gap between treatment at the institutional level and day-to-day living environment, by supporting the well-being of vulnerable people. In this paper, the literature as well as individual case studies are explored to better understand how therapeutic environments may enable the built infrastructure and transitional landscapes to fruitfully coexist. Findings suggest that suitable urban integration of services through therapeutic landscapes can provide a catalyst for the well-being of the wider community, mediating healthcare stigmas.